Penerapan Relaksasi Otot Progresif Dengan Penurunan Kadar Glukosa Darah Pada Pasien Diabetes Melitus Tipe II - Hana Ajeng Wahidya Paramita; Ida Nur Imamah; Sugito (An-Najat, 2024)
Background: Diabetes mellitus is a metabolic disease characterized by blood sugar instability caused by insufficient insulin secretion and action. Diabetes mellitus can be controlled through four pillars of management, one of which is physical activity such as progressive muscle relaxation. Progressive muscle relaxation is one of the nursing interventions that can be given to DM patients which involves regular muscle tightening and stretching to improve relaxation and self-management ability to lower blood sugar levels. Objective: Knowing the results of the application of progressive muscle relaxation with a decrease in blood glucose levels in patients with DM. Methods: Case study by comparing pre and post tests on 2 respondents conducted in May-June 2024. Results: Blood glucose levels before the application of progressive muscle relaxation in Mr. S were 452 mg/dl and 452 mg/dl. S is 452 mg/dl and after application it becomes 196 mg/dl while in Mrs. S before application it is 378 mg/dl and after application it becomes 193 mg/dl. Conclusion. There is a decrease in blood glucose levels before and after progressive muscle relaxation for 25-30 minutes in 4 days.